COVID-19 restrictions and hygiene measures reduce the rates of respiratory infections and wheezing among preterm infants - Scarponi, Davide; Bedetti, Luca; Zini, Tommaso; Di Martino, Marianna; Cingolani, Greta Miriam; Spaggiari, Eugenio; Rossi, Katia; Miselli, Francesca; Lugli, Licia; Bergamini, Barbara Maria; Iughetti, Lorenzo; Berardi, Alberto (Acta Biomedica Atenei Parmensis, 2023)
Background and aim: During the 2020 and 2021 Italian COVID-19 pandemic social restrictions and strict hygiene measures were recommended to limit the spread of SARS-CoV-2. We aimed to assess whether rates of respiratory infections and wheezing in preterm infants have changed during the pandemic. Methods: Single center, retrospective study. Preterm infants in the first 6 months of life discharged home prior to (Period 1, January 2017 - December 2019) or during the pandemic (Period 2, January 2020 - March 2021) were compared. Rates of respiratory infection and wheezing in preterm infants with or without bronchopulmonary dysplasia (BDP) were assessed. Results: During period 2 premature infants had lower rates of respiratory infections (36 out of 55 in Period 1 vs 11 out of 28 in Period 2, P=0.023) and wheezing (20 out of 55 in Period 1 vs 1 out of 28 in Period 2, P=0.001). This difference remained significant when infants with BPD (all grades) were analyzed separately (respiratory infections 26 out of 40 in Period 1 vs 7 out of 24 in Period 2, P=0.005; wheezing 16 out of 40 in Period 1 vs 1 out of 24 in Period 2, P=0.001). In contrast, respiratory infections and wheezing in preterm infants without BPD did not change after pandemic. Conclusions: Episodes of respiratory infections and wheezing among preterm infants were reduced during pandemic. We highlight the importance of proper family education for preventing respiratory tract infections in preterm infants with BPD, beyond the extraordinary conditions of the COVID-19 pandemic.